PENINGKATAN PEMBELAJARAN SENAM LANTAI GULING DEPAN MELALUI PERMAINAN PADA SISWA KELAS IV SD NEGERI 18 KOTA PEKANBARU - Sumarni, Titin (Jurnal Pendidikan Guru, 2017)
This study aims to improve the learning of the front rolling gymnastics through games on the fourth graders of SD Negeri 18 Pekanbaru. This research was conducted at SD Negeri 18 Kota Pekanbaru. The subject of this research is the fourth grade students of SD Negeri 18 Pekanbaru T.A 2015/2016. The fourth grade students of SD Negeri 18 Pekanbaru consist of 33 students consisting of 17 male students and 16 female students. Technique used to collect data in this research is test, and non test. This study was conducted by applying the modification game approach that has been done with 2 cycles, it can be concluded that the learning by applying the modification game approach has the average value of students on the initial condition of 70.46 with the percentage of mastery of 42.42%. The condition has increased the average value of students in the first cycle that is equal to 72.32 and the percentage of completeness of 57.69%. However, the increase has not yet reached the target set previously. Then after continuing to cycle II, the average score of students front-floor gymnastics ability again increased by 83.43 with the percentage of mastery of 81.82%. The conclusion that the application of the game modification approach improves the learning outcomes of the front roll gymnastics subjects penjaskes fourth grade students SD Negeri 18 Pekanbaru.